Hydrographic Nodality as Index for Predicting Fish Species Richness in West African Riverine Ecosystems - R. P. King; A. O. Ekwu; I. E. Ekpo (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to present the hydrographic nodality (N) and fish species richness (FSR) to evaluate the N-FSR relationships for West African riverine ecosystems using six Predictive Expressions (the Linear Line, Power Curve, Exponential Curve, Logarithmic Curve, Parabola and Cubic Curves). Of these models, the exponential curve, cubic curve, logarithmic curve and parabola curve were found to be adequate for FSR prediction in terms of their high degree of fitness to the data points and high forecasting efficiencies.  These are given respectively as: FSR = 47.811e0.0102N, FSR = 0.0035N3 – 1.0029N2 +78.995N + 155.62; FSR = 16.02LnN +78.92; and FSR = 0.2191N2 +48.118N + 292.92.